Insecticidal potential of defense metabolites from ocimum kilimandscharicum against helicoverpa armigera - Singh, Priyanka; Jayaramaiah, Ramesha H.; Sarate, Priya; Thulasiram, Hirekodathakallu V.; Kulkarni, Mahesh J.; Giri, Ashok P. (Plos One, 2014)
Genus Ocimum contains a reservoir of diverse secondary metabolites, which are known for their defense and medicinal value. However, the defense-related metabolites from this genus have not been studied in depth. To gain deeper insight into inducible defense metabolites, we examined the overall biochemical and metabolic changes in Ocimum kilimandscharicum that occurred in response to the feeding of Helicoverpa armigera larvae. Metabolic analysis revealed that the primary and secondary metabolism of local and systemic tissues in O. kilimandscharicum was severely affected following larval infestation. Moreover, levels of specific secondary metabolites like camphor, limonene and beta-caryophyllene (known to be involved in defense) significantly increased in leaves upon insect attack. Choice assays conducted by exposing H. armigera larvae on O. kilimandscharicum and tomato leaves, demonstrated that O. kilimandscharicum significantly deters larval feeding. Further, when larvae were fed on O. kilimandscharicum leaves, average body weight decreased and mortality the larvae increased. Larvae fed on artificial diet supplemented with O. kilimandscharicum leaf extract, camphor, limonene and beta-caryophyllene showed growth retardation, increased mortality rates and pupal deformities. Digestive enzymes of H. armigera - namely, amylase, protease and lipase- showed variable patterns after feeding on O. kilimandscharicum, which implies striving of the larvae to attain required nutrition for growth, development and metamorphosis. Evidently, selected metabolites from O. kilimandscharicum possess significant insecticidal activity.